Ліпний посуд як елемент поховальної обрядності населення скіфського часу Дніпро-Донецького Лісостепу - Пеляшенко, К.Ю. (My University, 2012)
K. Peliashenko. Moulded Vessels as Funerary Rites Element of Dnipro-Donets Foreststeppe Populace in Scythian Time The article examines the role of moulded ceramics in funerary rites of Dnipro-Donets forest-steppe tribes in Scythian time. Differences in the tradition of the vessels location in burial interment of different population groups are established with the help of age, sex and social characteristics of the complexes. Analysis of all the features of vessels placement in the grave space, including nonstandard (facts of turning upside down, putting one vessel into another, breaking, etc.), suggests that the use of vessels in the funerary practice had differentiated nature and was not limited only by the farewell food placement.
Keywords: molded vessels; the Dnipro-Donets forest-steppe; Scythian time; age, gender and social analysis; funerary complexes